Advances in Mechanical and Energy Technology Select Proceedings of ICMET 2021 - Yadav, Sanjay; Jain, Prashant Kumar; Kankar, Pavan Kumar; Shrivastava, Yogesh (Springer Nature Singapore, 2023)
This book presents the select proceedings the 2nd International Conference on Mechanical and Energy Technologies (ICMET 2021). The broad range of topics and issues covered are bulk deformation processes and sheet metal forming, composites, ceramics, and polymers processing, corrosion, heat treatment, microstructure and materials properties, energy materials, failure and fracture mechanics, friction, wear, tribology, and surface engineering, functionally graded materials, cellular materials, low friction and corrosion resistive materials for energy applications, lubricants and lubrication, machinability and formability of materials, material science and engineering, and materials for energy storage. This book will be useful for students, researchers, and professionals working in the areas of mechanical and industrial engineering, energy technologies, and allied fields.
Application of Taguchi Approach to Optimize the Robot Spot Welding Parameters of JSC590RN Mild Steel -- Taguchi with GRA Based Optimization of Machining Parameters for End Milling of SS-304 -- Design and Analysis of Knuckle Pin using Different Materials in Ansys -- The Current State and Potential of Canal-top Solar Power Plant in India -- Weapon Detection Rope Roaming Human Safety Robot -- Review and Real World Usability of Magnetic Levitation Trains -- Entrepreneurial Women in the Culture of Ceará: The Case of Cearens Literature -- Machining of Composite Materials using Different Conventional and Unconventional Machining Processes: A Short Review -- An Investigation on Effect of Hybrid Nanofluids in End Milling of Aluminium 6061 Alloy -- Classification Methods for Labelled Data in Machine Learning -- A Review of Solar Refrigeration for Cooling Applications
Keywords: Electric power production; Renewable energy sources; Materials; Mechanics, Applied